Simulation of three intraoral radiographic techniques in pediatric dental patients: subjective comfort assessment using the VAS and Wong-Baker FACES Pain Raiting Scale - (:unkn) unknown (BMC, 2020)
BackgroundPerception of pain associated with intraoral radiography in pediatric patients was evaluated through statistical comparisons of data obtained using the Wong-Baker FACES Pain Raiting Scale (WBFPRS) and visual analog scale (VAS) scoring.MethodsA total of 75 pediatric patients aged 6-12years were included in this study. Simulations of each of three radiological methods (analog films, CCD sensor and phosphorus plates) were performed on 25 pediatric patients. Following the simulations, the meaning of each facial expression on the WBFPRS and the numbers on the VAS were explained to each child. For the comparison between groups, the homogeneity of the variances was tested with Levene's test; because the variances were not homogeneous, Welch's test was used. Tamhane's T2 test was used because the homogeneity assumption was not provided to determine the source of the difference between the groups.ResultsWhen the conventional method was compared to the PSPL (photostimulable phosphor luminescence) method, no significant differences were noted in either the WBFPRS or VAS results (p >0.05). The results obtained from both of the scales were significantly different between the conventional method and the CCD sensor method (p<0.05). When the PSPL and CCD sensors were compared, a significant difference was observed for the WBFPRS (p<0.05). It was found the highest level of pain scores when used the CCD sensor method than the analog film and PSPL methods (p<0.05).ConclusionsIt is expected that digital radiographic techniques will be improved in the future and that their disadvantages will be eliminated, resulting in imaging devices that are more comfortable for pediatric patients.
Keywords: Radiography; Dental; Pediatric patient; Comfort assessment; DIGITAL RADIOGRAPHY; DENTISTRY